A discourse-functional description of participant reference in Biblical Hebrew narrative - Runge, Steven Edward (Stellenbosch : Stellenbosch University, 2008)
Thesis (DLitt (Ancient Studies. Biblical Languages))--Stellenbosch University, 2007.